2017
DOI: 10.21859/mci-01042
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Coping Strategies after Diagnosis: A Six-month Follow-up

Abstract: Introduction: Breast cancer is a tragic experience that accompanies stressful situations for patients. Adjustment with breast cancer has a significant effect on decreasing stress and increasing the patients› quality of life. Methods: In a prospective cross-sectional study, breast cancer patients› experiences were evaluated at Breast Cancer Research Center (BCRC), Motamed Cancer Institut (MCI), Tehran, Iran. To evaluate coping strategies in breast cancer patients, a modified Ways of Coping-cancer Version (WOC-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
(48 reference statements)
3
13
0
2
Order By: Relevance
“…3,6 Sajadian and colleagues noted no significant association between coping and demographic characteristics in breast cancer patients. 29 The clinical features, duration of illness, and adjuvant therapy were associated with anxious preoccupation in the adjustment to cancer in our studies, as was also reported in earlier studies. 30 We also found that perceived social support was associated with the adjustment to cancer-specifically, FS and fatalism.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3,6 Sajadian and colleagues noted no significant association between coping and demographic characteristics in breast cancer patients. 29 The clinical features, duration of illness, and adjuvant therapy were associated with anxious preoccupation in the adjustment to cancer in our studies, as was also reported in earlier studies. 30 We also found that perceived social support was associated with the adjustment to cancer-specifically, FS and fatalism.…”
Section: Discussionsupporting
confidence: 89%
“…A Malaysian study reported a strong relationship between increased age, low income and low educational status, and fatalistic features . Sajadian and colleagues noted no significant association between coping and demographic characteristics in breast cancer patients . The clinical features, duration of illness, and adjuvant therapy were associated with anxious preoccupation in the adjustment to cancer in our studies, as was also reported in earlier studies …”
Section: Discussionsupporting
confidence: 89%
“…Studies have revealed that for women with breast cancer, factors such as age, stage of disease, educational level, method of treatment, and social support impact on coping with stress. The use of strategies for coping with stress is related to perceptions of increased social support after receiving a diagnosis of breast cancer . It is reported that the social support provided to women with breast cancer has a major effect in coping with stress .…”
Section: Introductionmentioning
confidence: 99%
“…for coping with stress is related to perceptions of increased social support after receiving a diagnosis of breast cancer. 4,12,13 It is reported that the social support provided to women with breast cancer has a major effect in coping with stress. 14 Social support enables women to gain a positive point of view on their medical condition and cope with their disease better, and it also increases the effectiveness of treatment.…”
mentioning
confidence: 99%
“…Sajadian ve ark. (35) meme kanserli hastalarla yürüttüğü çalışmada, daha çok stres yaşayan hastaların başa çıkma stratejilerini de daha sık kullandığını saptamıştır. Literatürde kanser hastalarında algılanan stres, stres belirtileri ve stresle başa çıkma arasındaki korelasyonu birebir değerlendiren çalışmaya rastlanmamıştır.…”
Section: Verilerin Analiziunclassified